Foreign direct investment and economic growth in South Africa: a sector level causality analysis - Maseko, Michael (Research of GSB, 2018)
Many empirical studies hypothesise that foreign direct investment (FDI) has a positive impact on economic growth. As a result, FDI has been targeted by many countries in their attempts to increase their standards of economic growth. South Africa (like many developing economies) is not a stranger to this phenomenon. However, there is a dearth of literature analysing the relationship between FDI and economic growth at a sector level in South Africa. This thesis analyses the causal relationship between FDI and economic growth in South Africa at a sector level comprising primary, secondary and tertiary industries. This study applied a more robust and asymptotically reliable Toda-Yamamoto-Dolado-Lutkephol (1995) methodology in analysing the causal relationship thus addressing the potential biases and asymptotic unreliability relating the traditional Granger causality technique. The report shows that FDI Granger-causes growth in primary, secondary, tertiary sectors and at an aggregate level. In addition, growth was found to Granger-cause FDI at tertiary and aggregate level. On the other hand growth does not Granger-cause FDI at primary and secondary sector level. The only bi-directional relationship that could be observed was at the tertiary and aggregate sector level, whereas at primary and secondary sector level, the relationship was found to be unidirectional.